Hemagglutinin-neuraminidase and fusion proteins of virulent Newcastle disease virus cooperatively disturb fusion–fission homeostasis to enhance mitochondrial function by activating the unfolded protein response of endoplasmic reticulum and mitochondrial stress - Ren, Shanhui (Vet Res, 2019)
The fusogenically activated F and HN proteins of virulent NDV induce complete autophagic flux in DF-1 and A549 cells. However, the effect of both glycoproteins on mitochondria remains elusive. Here, we found that F and HN cooperation increases mitochondrial biogenesis but does not cause the mitochondria damage. We observed that both glycoproteins change the morphological characteristics and spatial distribution of intracellular mitochondria. F and HN cooperate cooperatively to induce ER stress and UPR(mt). Our preliminary data suggested that F and HN cooperatively disturb mitochondrial fusion–fission homeostasis to enhance mitochondrial biogenesis, and eventually meet the energy demand of syncytium formation.